Endotoxicosis in Patients with Acute Intoxication with Psychotropic Drugs - Yu. A. Gryzunov; Ye. D. Syromyatnikova; K. K. Ilyashenko (Общая реаниматология, 2005)
A hundred and twenty-one patients with acute severe and critical intoxication with psychotropic agents were examined to assess the prognostic value of the laboratory parameters of endotoxicosis in this acute condition. Analysis of 24 laboratory parameters in the groups of survivors (n = 92) and dead patients (n = 29) indicated that these groups significantly differed only in 5 parameters: effective albumin concentration (EAC), total albumin concentration, serum creatinine concentration, serum urea concentration, and erythrocytic sedimentation rate. Statistical analysis of each parameter identified groups with a poor prognosis of the disease. In these groups, the death rate was significantly higher (p <0.05) than the apri-ori rate estimated as the average mortality rate in the whole study under examination. EAC demonstrated the highest prognostic value. The findings may serve as the basis for developing new methods to make an individual assessment of the health status of patients with acute intoxications with psychotropic drugs in the resuscitative period.